THE ORIENTATION OF THE DYNAMICAL FRAMES RELATIVE ICRF BY USE OF OPTICAL AND RADAR OBSERVATIONS NEAR-EARH ASTEROIDS (NEAs) - Yagudina, E. I. (Одеські астрономічні публікації, 2017)
ICRF (practical realization of ICRS) is now adopted as the fundamental celestial frame in astronomy. It is based on the positions of the extragalactic radio sources obtained by VLBI observations. Zero-point of right acsentions of ICRF was chosen in a such way that the right ascention of 3C273B quasar was taken from FK5 at the same epoch. The Hipparcos catalogue is the primary realization of the ICRF at optical wavelengths. The rigid model rotation of FK5 with respect to ICRF was adopted for connecting Hipparcos and FK5, the origin of ICRF axes is located at barycentre of the solar system. The dynamical systems (the DE ephemerides, JPL USA; EPM, Russia) are related to ICRF and at present this relation is at sub-milliarcsecond level. To provide the continuity of changing the reference systems, the main plane of the ICRF was chosen in such a way, that its orientation in space is within the range of errors characteristic of the ground observations, coincides with position of "dynamical"equator FK5 catalogue at J2000.0. At present new VLBI observations will give new sources for extending the ICRF as well as future space astrometry missions (DIVA, FAME. SIM etc.) for extention of ICRF over million stars. In spite of the fact that ICRF is a quasi-inertial system there are a great number of problems associated with the use of the ICRF, the main of them being the connection of ICRF to dynamical systems. The parameters of this connection are known with insufficient accuracy and further work is necessary on the problem of mutual orientation of these systems at the new level of accuracy using different new observations of different solar system objects. For this purpose radar and optical observations of the asteroids (mainly Near Earth Asteroids-NEAs) have been used. The combined solution gave us six parameter orientations which are in good agreement with another authors.